Corporate Governance Characteristics dan Business Ethics Disclosure: Sebuah Studi Pada Perusahaan Manufaktur di Indonesia - Siboro, Christinari Nancy; Siregar, Anitaria (Juara: Jurnal Riset Akuntansi, 2024)
Business ethics violations in Indonesia, such as PT Kimia Farma Tbk.'s inflated income case, highlight the need to examine corporate governance's influence on business ethics implementation, as reflected in disclosures. Good corporate governance could create an environment which pushes the company to practice business ethics with a high ethics standard. Corporate governance characteristics which use consists of ownership concentration, board independence, government ownership, board gender diversity, and managerial ownership. The sample of this study consists of 100 manufacture companies which listed in Indonesia Stock Exchange for the 2020 to 2022 observation year. The result shows that corporate governance characteristic, named government ownership, has a significant positive influence towards business ethics disclosure. Furthermore, the other corporate governance characteristics which consist of ownership concentration, board independence, board gender diversity, and managerial ownership do not have the significant influence towards business ethics disclosure. The result also shown that the disclosure of business ethic is still low for manufacture companies in Indonesia.